Maternal smoking before and during pregnancy and the risk of sudden unexpected infant death - Anderson, Tatiana M.; Lavista Ferres, Juan M.; Ren, Shirley You; Moon, Rachel Y.; Goldstein, Richard D.; Ramirez, Jan-Marino; Mitchell, Edwin A. (Pediatrics, 2019)
OBJECTIVES: Maternal smoking during pregnancy is an established risk factor for sudden unexpected infant death (SUID). Here, we aim to investigate the effects of maternal prepregnancy smoking, reduction during pregnancy, and smoking during pregnancy on SUID rates. METHODS: We analyzed the Centers for Disease Control and Prevention Birth Cohort Linked Birth/Infant Death Data Set (2007–2011: 20 685 463 births and 19 127 SUIDs). SUID was defined as deaths at <1 year of age with International Classification of Diseases, 10th Revision codes R95 (sudden infant death syndrome), R99 (ill-defined or unknown cause), or W75 (accidental suffocation or strangulation in bed). RESULTS: SUID risk more than doubled (adjusted odds ratio [aOR] = 2.44; 95% confidence interval [CI] 2.31–2.57) with any maternal smoking during pregnancy and increased twofold between no smoking and smoking 1 cigarette daily throughout pregnancy. For 1 to 20 cigarettes per day, the probability of SUID increased linearly, with each additional cigarette smoked per day increasing the odds by 0.07 from 1 to 20 cigarettes; beyond 20 cigarettes, the relationship plateaued. Mothers who quit or reduced their smoking decreased their odds compared with those who continued smoking (reduced: aOR = 0.88, 95% CI 0.79–0.98; quit: aOR = 0.77, 95% CI 0.67–0.87). If we assume causality, 22% of SUIDs in the United States can be directly attributed to maternal smoking during pregnancy. CONCLUSIONS: These data support the need for smoking cessation before pregnancy. If no women smoked in pregnancy, SUID rates in the United States could be reduced substantially.